2015
DOI: 10.1039/c5sc00835b
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed asymmetric hydrogenation of fluorinated aromatic pyrazol-5-ols via capture of active tautomers

Abstract: Here we explore a novel strategy for asymmetric hydrogenation of aromatic pyrazol-5-ols via capture of the active tautomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…Very recently, Zhou et al reported the asymmetric hydrogenation of fluorinated pyrazol‐5‐ols by capturing one of the tautomers with the aid of a strong Brønsted acid as activator. Two catalytic systems were developed for 4‐unsubstituted of 4‐substituted pyrazol‐5‐ols, based on the use of ligand L12 or L13 and TFA or L ‐CSA as activators, respectively (Scheme , g) 47. The hydrogenation of 17 examples was reported, with overall enantioselectivity in the corresponding substituted hydrogenated compounds ranging from 82 to 96 % ee .…”
Section: Strategy Iii: Hydrogenation After Breaking the Aromaticitymentioning
confidence: 99%
“…Very recently, Zhou et al reported the asymmetric hydrogenation of fluorinated pyrazol‐5‐ols by capturing one of the tautomers with the aid of a strong Brønsted acid as activator. Two catalytic systems were developed for 4‐unsubstituted of 4‐substituted pyrazol‐5‐ols, based on the use of ligand L12 or L13 and TFA or L ‐CSA as activators, respectively (Scheme , g) 47. The hydrogenation of 17 examples was reported, with overall enantioselectivity in the corresponding substituted hydrogenated compounds ranging from 82 to 96 % ee .…”
Section: Strategy Iii: Hydrogenation After Breaking the Aromaticitymentioning
confidence: 99%
“…[14,15] Therefore, the selective transformationo fisoxazoles to isoxazolines or isoxazolidinesi saformidable task in organic chemistry. [16] The asymmetric hydrogenationo fi soxazoles is au seful method to prepare optically active isoxazolines or isoxazolidines.T hese compoundsa re often used as intermediates in the syntheses of usefulc ompounds. [17,18] The isoxazoline or isoxazolidine framework is found in some biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research have demonstrated that Brønsted acids often play as promoter to facilitate the hydrogenation through activating substrate [13] and accelerating imine-enamine [9f] or hydroxy-oxo tautomerization. [14] In addition, much progresses have been successfully achieved in palladiumcatalyzed asymmetric hydrogenation, which feature ar obust hydrogenation catalyst with high toleration to the strong Brønsted acid, oxygen and moisture. [15][16][17] Thus,i nitially,w e choose readily available 4-phenylpyrimidin-2-ol (1a)a s model substrate,P d(OCOCF 3 ) 2 /(S)-Synphos (L1)c omplex as hydrogenation catalyst and trifluoroacetic acid (TFA) as additive.The hydrogenation was run in toluene at 60 8 8Cunder 1000 psi of hydrogen.…”
mentioning
confidence: 99%